A new electronically tunable universal mixed-mode biquad filter - Singh S.V.; Tomar R.S.; Chauhan D.S. (My University, 2025)
This paper introduces a new electronically tunable universal mixed-mode biquad filter topology, which mainly consists of single newly introduced modified current conveyor trans-conductance amplifier (MCCTA) as active element and two capacitors, two resistors as passive elements. The filter topology can realize low pass (LP), band pass (BP), high pass (HP), band reject (BR) and all pass (AP) filtering responses in four different possible modes of operation namely, current-mode (CM), voltage-mode (VM), trans-impedance-mode (TIM), and trans-admittance-mode (TAM), through applying appropriate conditions and selection of inputs and outputs. While operating, the circuit does not need any inverted type and/or scaled type current/voltage input signal(s) for any of the filtering response realization. It is also encouraging to sustain the feature of interactive electronic tunability of quality factor as well as band-width independent of pole frequency variation, only through single biasing current of the active element. The proposed filter is simulated through PSPICE software using standard CMOS technology and offers low incremental active and passive sensitivities.